2005
DOI: 10.1515/bc.2005.108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cathepsin B reduces β-amyloid production in regulated secretory vesicles of neuronal chromaffin cells: evidence for cathepsin B as a candidate β-secretase of Alzheimer's disease

Abstract: The regulated secretory pathway of neurons is the major source of extracellular A beta that accumulates in Alzheimer's disease (AD). Extracellular A beta secreted from that pathway is generated by beta-secretase processing of amyloid precursor protein (APP). Previously, cysteine protease activity was demonstrated as the major beta-secretase activity in regulated secretory vesicles of neuronal chromaffin cells. In this study, the representative cysteine protease activity in these secretory vesicles was purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 13 publications
5
121
1
1
Order By: Relevance
“…Results indicating cathepsin B as a β-secretase in regulated secretory vesicles (Hook et al, 2005), combined with evidence for BACE 1 as β-secretase for basal and constitutive secretion of Aβ, are consistent with the unifying hypothesis for distinct proteolytic pathways for β-secretase processing of APP (Fig. 7).…”
Section: Unifying Hypothesis For β-Secretase Activities By Cathepsin supporting
confidence: 79%
See 3 more Smart Citations
“…Results indicating cathepsin B as a β-secretase in regulated secretory vesicles (Hook et al, 2005), combined with evidence for BACE 1 as β-secretase for basal and constitutive secretion of Aβ, are consistent with the unifying hypothesis for distinct proteolytic pathways for β-secretase processing of APP (Fig. 7).…”
Section: Unifying Hypothesis For β-Secretase Activities By Cathepsin supporting
confidence: 79%
“…The regulated secretion of neuronal Aβ is induced by receptor-mediated activation of neurons (Nitsch et al, 1993;Farber et al, 1995;Wolf et al, 1995;Efthimiopoulos et al, 1996;Jolly-Tornetta et al, 1998;Hook et al, 2002). Compared to the major regulated secretory pathway for Aβ production and secretion, a minor portion of Aβ undergoes basal secretion from the constitutive secretory pathway (Hook et al, 2002(Hook et al, , 2005.…”
Section: Alzheimer's Disease Involves Proteases That Produce Neurotoxmentioning
confidence: 99%
See 2 more Smart Citations
“…In primary cultures of chromaffin cells, the cell permeable cysteine protease inhibitor E64d was also shown to inhibit the production of the APPderived COOH-terminal b-secretase cleavage product. Previous reports have also concluded that cathepsin B and CysLT1R are involved in AD development and progression [11]. However, the relationship between cathepsin B and CysLT1R activity is not clear.…”
Section: Introductionmentioning
confidence: 98%